Do Materialistic Consumers Buy More During the COVID-19 Pandemic?: Social Consumption Motivation of Anxious Malaysians in the Face of Existential Threat of Death - Toh, Seong-Yuen *; Yuan, Siew-Wai; Kaur, Ranita* (IGI Global, 2022)
This study investigates the mediated moderating relationship of self-concept clarity, materialism, and social consumption motivation in the context of COVID-19 pandemic based on the terror management theory. The findings suggest that Malaysian consumers have high self-concept clarity about their materialistic orientation. This materialistic orientation may be of hedonistic-utilitarian nature that is internally directed for self-satisfaction and not exclusively directed externally in material consumption to portray an image to others. Furthermore, this study posits that cultural factors like collectivism and uncertainty avoidance delimits the applicability of terror management theory in Malaysia,suggesting that the development of the theory draw heavily from Western ideology of individualism not directly relevant in the Asian context. Finally, this study offers an understanding of the self-concept clarity from the Asian context, addressing the appeal by Dunlop to investigate the construct of self-concept clarity particularly in non-Western context